THE IMPACT OF DIGITAL MARKETING AND BRAND IMAGE ON CONSUMER DECISIONS REGARDING THE PURCHASE OF AIRASIA AIRLINE TICKETS - Dedeng Abdul Gani Amruloh; Yulianto, Wahyu; Imam Munandar, Atep (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
The objective of this research was to ascertain the impact of consumer purchasing decisions for Air Asia flight tickets. In this study, the variables of digital marketing and brand image are employed as dependent variables. Primary data were collected using non-probability sampling techniques, which do not provide equal opportunities for each element or member of the population to be selected as a sample. The sample used in this research consisted of 97 individuals. The data analysis method employed in this research is multiple linear regression. The findings of the research indicate that digital marketing and brand image have a positive and significant impact on purchasing decisions, to some extent. The calculated F-value of 50.839 with a significance level of 0.000 < 0.05 indicates that the entire dependent variable exerts a simultaneous effect on purchasing decisions. The R-squared value demonstrates that the entire dependent variable accounts for a simultaneous effect of 52.0%.